Double seronegative myasthenia gravis with low density lipoprotein-4 (LRP4) antibodies presenting with isolated ocular symptoms - Tsivgoulis, Georgios; Dervenoulas, Georgios; Kokotis, Panagiotis; Zompola, Christina; Tzartos, John S; Tzartos, Socrates J; Voumvourakis, Konstantinos I (Journal of the neurological sciences, 2014)
The detection of low density lipoprotein-4 (LRP4) antibodies in double seronegative (dSN) myasthenia gravis (MG) patients has provided new insights in the diagnosis and treatment of MG. However, there are limited data regarding the clinical presentation and treatment response in dSN MG patients with LRP4-antibodies. We present a case series of three Caucasian dSN MG patients with positive LRP4-antibodies sharing a common ethnic background that presented with isolated ocular symptoms (MGFA I). The demographic and clinical characteristics, the diagnostic work-up as well as the treatment response during a follow-up period of 12-24 months are described in detail. All patients were treated successfully with acetylcholinesterase inhibitors (AcheI) and prednisone with two exhibiting full remission of their symptoms, while the remaining exhibited mild residual diplopia. Notably, we documented no signs of generalized disease progression, while no patient required immunosuppressive treatment. In conclusion, the distinct clinical phenotype of our patients highlights the clinical relevance of screening for LRP4-antibodies in patients presenting with isolated ocular MG independent of age and gender, since it may lead to the timely diagnosis of MG and prompt initiation of effective therapy with ACheI and corticosteroids.
Keywords: dospělí; prednison; Female; proteiny související s LDL-receptory; Adult; výsledek terapie; myasthenia gravis; ženské pohlaví; Diplopia; lidé; glukokortikoidy; Glucocorticoids; Prednisone; Aged, 80 and over; Treatment Outcome; Myasthenia Gravis; blefaroptóza; Pyridostigmine Bromide; Blepharoptosis; Male; diplopie; pyridostigmin-bromid; LDL-Receptor Related Proteins; kombinovaná farmakoterapie; lidé středního věku; senioři nad 80 let; mužské pohlaví; cholinesterasové inhibitory; Cholinesterase Inhibitors; Middle Aged; Drug Therapy, Combination; Humans